Exploring Faculty and Student Reflections on Collaborative Teaching in the Honors Seminar Classroom - Looft, Ruxandra; Myers, Megan Jeanette (Journal of Interdisciplinary Studies in Education, 2019)
University Honors programming in the United States is interdisciplinary and collaborative; from First Year Honors Seminars to capstone research projects for upperclassmen, Honors students embrace multidisciplinary learning and research. This approach, however, does not always translate into the Honors classroom in regards to an incorporation of diverse perspectives of multiple faculty members in a given course. This article utilizes a mixed-methods approach to explore the impact and results of a collaboratively taught Honors Seminar. “Exploring Faculty and Student Reflections on Collaborative Teaching in the Honors Seminar Classroom” departs from the authors’ model of a co-taught Honors Seminar and then moves to an exploration of the student responses, comparing both a pre- and post-course survey, that considers student perceptions of multi-instructor formats. The essay ends with a brief conclusion that addresses some possible challenges to team-taught courses, from scheduling to institutional issues, in the context of Honors programming in an effort to encourage continued discussion about collaborative teaching of Honors Seminars.